Sunda Wiwitan Baduy: Agama Penjaga Alam Lindung di Desa Kanekes Banten - Masykur Wahid (UIN Maulana Malik Ibrahim Malang, 2011)
Baduy-style Islamic is pronounced with syahadat and practiced with tapa to maintain and preserve the natural heritage, karuhun. Tapa of Baduy is working in the fields to plant rice as a form to practice Islamic teachings, by mating the goddess of rice to the earth. Baduy’s action was guided by the pikukuh, custom, following the buyut, taboo. Religious teachings, tapa, pikukuh and buyut have shaped simple personalities Baduy people in maintaining the Kanekes natural conservation. Thus, welfare and peace can be felt by mankind. This paper describes the system of religion and religious rituals Sunda Wiwitan. In the perspective of religion phenomenology issue, the phenomena are studied using direct observation method and in-depth interviews. One of the finding illustrated that the Baduy people’s faith and obedience to God appears in their actions in taking care of forests, rivers and mountain to life in harmony. Their faith is not in the form of memorizing or interpreting old religious scripture. Furthermore, worship rituals are practiced by working in the fields under custom rules guidance and abiding the taboo to have successful harvest and prosperous people. Worship is not intended to become a respected man or benefactor. This is the Sunda Wiwitan people with life perspective of maintaining the Kanekes natural conservation.Islam ala Baduy diucapkan dengan syahadat dan diamalkan dengan tapa untuk menjaga dan melestarikan alam warisan karuhun, nenek moyang. Tapa Baduy adalah bekerja di ladang dengan menanam padi sebagai amalan ajaran agama, mengawinkan dewi padi dengan bumi. Tindakan masyarakat Baduy itu berpedoman kepada pikukuh, aturan adat, dengan mematuhi buyut, tabu. Ajaran agama, tapa, pikukuh dan buyut telah mengkonstruksi pribadi-pribadi Baduy yang sederhana dalam menjaga alam lindung Kanekes. Sehingga, kesejahteraan dan kedamaian dapat dirasakan oleh umat manusia. Tulisan ini memaparkan sistem religi dan ritual keagamaan Sunda Wiwitan. Dalam perspektif fenomenologi agama permasalahan itu dikaji dengan metode observasi terlibat langsung dan wawancara mendalam. Ditemukan jawaban bahwa keimanan dan ketaatan umat Baduy kepada Allah tampak dalam tindakan mereka menjaga hutan, sungai dan gunung hidup harmoni. Keimanannya bukan dalam hafalan ataupun penafsiran kitab suci. Sedangkan, 2 ibadah ritualnya dipraktikkan lewat bekerja di ladang dengan aturan adat dan patuh pada tabu supaya panen berhasil dan umat sejahtera. Ibadahnya bukan ingin menjadi manusia yang dihormati ataupun dermawan. Inilah umat Sunda Wiwitan dengan pandangan hidup menjaga alam lindung Kanekes